Helen Keller papers - Keller, Helen, 1880-1968.
Correspondence, speeches and writings, clippings, printed matter, and photographs. The correspondence consists chiefly of files of Swedenborgian minister Paul Sperry relating to publication of Keller's book, My Religion (1962). Newspaper clippings, U.S. Dept. of State dispatches, and speeches document Keller's trip to South America in 1954. Includes drafts of writings by Evelyn M. Watson and others.
Author and lecturer.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Sperry, Paul, -- 1879-1954.; Swedenborg, Emanuel, -- 1688-1772.; Watson, Evelyn M. -- 1886-1956.; Blind authors; New Jerusalem Church; South America -- Description and travel